A fluorous sodium l-prolinate derivative as low molecular weight gelator for perfluorocarbons. Issue 61 (30th June 2020) - Beniazza, Redouane; Bayo, Natalia; Jardel, Damien; Rust, Ruben; Mao, Bosi; Divoux, Thibaut; Schmutz, Marc; Castet, Frédéric; Raffy, Guillaume; Del Guerzo, André; McClenaghan, Nathan D.; Buffeteau, Thierry; et al.
Abstract : The fluorous sodium l -prolinate 1 self-assembles in perfluorocarbons to form a three-dimensional network of left-handed nano-helices resulting in solvent gelation. Abstract : We report the first study dealing with the self-assembly of an α-amino acid derivative in perfluorocarbons. Rheology, microscopy, and spectroscopy studies reveal that the fluorous sodium l -prolinate derivative 1 self-assembles in perfluorocarbons to form a three-dimensional network of left-handed nano-helices resulting in solvent gelation. Singlet oxygen lifetime measured in a gel of perfluorodecalin is about 1000 times longer than in pure water.